ab initio X-ray structure determination of NaAl(SO4)2 (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
The sodium aluminium disulphate NaAl(SO4)2 has been obtained after calcinations at 300 °C of NaAl(SO4)2.12H2O alum. The structure of this compound has been refined from powder       X-ray diffraction data using the Rietveld method. This compound crystallises in trigonal system       P 3 2 1 with the following parameters: a = 4.749(12) Å, c = 8.314 (4) Å (Z = 1).  The final refinement led to RF = 6.3 %, RB = 4.12 %. In the proposed model the sulfate ions is in disorder between two nonequivalent crystallographic sites with probabilities p1/p2= 0.30/70. The atomic arrangement of NaAl(SO4)2 is characterised by two different alternating layers parallel to (001): the first layer is composed of corner-linked AlO6 octhahedra and SO4 tetrahedra, the second layer is built from monovalent Na+ .